Systematic Literature Review terkait Learning Obstacles Siswa SMP pada Pemahaman Konsep Aljabar - Qonita Tri Maulina; Halimatu Sa'diyyah; Cita Dwi Rosita; Wahyu Hartono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Learning obstacles faced when solving math problems have become an exciting topic to research. This is due to the importance of developing mathematical concepts and understanding skills, especially algebraic concepts. This study aims to describe the research results related to junior high school students learning obstacles in understanding algebraic concepts. This research uses the Systematic Literature Review (SLR) method, comprising 22 studies. This study concludes that research related to junior high school students learning obstacles in understanding algebra concepts is found most in Sinta publications, then continued with Scopus, EBSCO, Proceeding, and DOAJ. These studies include a variety of methods used, with the Didactical Design Research approach dominating. Epistemological, didactical, and ontogenic barriers were the main concerns, with didactical obstacles being the most common in this study. These obstacles include the lack of direct interaction and active learning between teachers and students and the lack of optimal use of varied learning methods and teaching aids, causing students to have difficulty in planning problem-solving strategies, solving story problems, and understanding mathematical concepts thoroughly. Concrete efforts that can be made to overcome the identified obstacles include utilizing active, collaborative, and exploratory learning approaches.